Non-adaequatio: Negative Dialectics in-between Kant and Hegel - Pocius, Audrius (Problemos, 2023)
The aim of this article is to frame Adorno’s concept of ‘nonidentity’ in the context of German idealism, namely, the philosophies of Kant and Hegel. The thesis to be defended is that “Secularization of Metaphysics” entails relinquishing, as well as prolongation of the German idealist tradition. The argument is developed in the following steps: 1) the constitution of an autonomous transcendental subject is shown to be rooted in the idea of Enlightenment; 2) by reconstructing Adorno’s conception of truth as non-adaequatio, I claim that Adorno’s philosophy is conducted from the perspective of the end of philosophy; 3) the sociohistorical character of the concept of ‘nonidentity’ is discussed in relation to Adorno’s understanding of history; 4) the concept of ‘nonidentity’ is discussed as implying a continuation of the Kantian project on a metacritical level; 5) Adorno’s critique of Kant is reconstructed in the context of Hegel’s Faith and Knowledge.